The Potential of Mahligai's Tomb as a Religious Tourism Destination in Barus North Sumatera - Sukma, Pelita; Mardiah, Imay; Syahrani, Nilam; Yufrizal, Yufrizal (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
This article aims to examine the potential of the Makam Mahligai as a religious tourism destination in Barus, North Sumatera because it reviews its historical aspect and its location is very worthy of professional development so that it becomes one of the regional icons whose notabene is an early area that comes into contact with the propagator of Islam. It is carried out with a qualitative method that leads to content analysis as the end of the research activity. In addition to using literature studies, field studies were also carried out to the location that became the object of the study. The final result concluded that the Makam Mahligai in Barus, North Sumatera, is an important historical site that represents the beginning of the entry of Islam into the archipelago since the 7th century AD. Barus as a large trading port became the center of cultural and religious interaction between Muslim traders from Arabia, India and China with the local community. The Makam Mahligai has tombs with various types of tombstones that existed at the time as historical and cultural and archaeological evidence that can be realized as a religious tourist destination. The potential of the Makam Mahligai as a religious tourism destination is huge, because it combines spiritual, historical, and cultural aspects. It can even provide opportunities to enrich the spiritual experience of visitors, introduce local traditions, and encourage economic growth of the surrounding community. For Future Research, it is recommended to conduct a more in-depth study involving community participation and the role of local government in the development of religious tourism. Further research may also explore the vicitor experience, sustainable tourism practies, and integration of technology in promoting and preserving the Makam Mahligai site.